Attracting Foreign Investment is the Foundation of Development - Islomjon Nurmuxammadov Xunimuxammad o’g’li (Miasto Przyszłości, 2023)
The article deals with the attraction of foreign investments processes have been studied. Attracting foreign investment within the framework of ways to make and use them effectively existing deficiencies are identified. To the national economy foreign investment attraction system scientific proposal and practical recommendations for improvement formed.